Corporate communication for Vietnamese listed firms - Scully, Glennda; Tower, Greg; Vu, K.A. (emerald, 2011)
Purpose – The purpose of this paper is to investigate the impact of independent directors and ownership structure on voluntary disclosures of Vietnamese listed firms. Design/methodology/approach – Year-ending 2008 annual report disclosures of 45 Vietnamese listed firms are analyzed. Voluntary disclosure is measured using a Vietnamese Disclosure Index adapted from prior literature. Descriptive and inferential statistics (T-test, analysis of variance, multiple regressions (ordinary least squares)) are employed to generate empirical insights. Findings – The results indicate that the level of voluntary disclosure among Vietnamese listed firms is relatively low (24.23 per cent). There are higher levels of disclosure relating to director and senior management details but far lower in regards to social issues. State ownership and managerial ownership are negatively and positively related to the extent of voluntary disclosure respectively.Moreover, bigger firms are found to be positively associated with voluntary disclosure. Research limitations/implications – The results of this study are limited to one year – 2008 – and thus, could be biased as disclosures can change over time. Practical implications – Vietnamese regulators should focus on strengthening the regulations governing the level of corporate communication in firms with high state ownership as well as encouraging more disclosure of non-financial information to strengthen its market information transparency.Originality/value – This study is one of the first examining the level of corporate voluntary disclosure practices among Vietnamese listed firms. Evidence from this study extends the existing voluntary disclosure literature on emerging economies whilst providing valuable insights to Vietnamese policy makers in the process of developing and improving its financial reporting regulatory framework.